Comparison of neoadjuvant versus a surgery first approach for gastric and esophagogastric cancer. Issue 3 (11th August 2016) - Russell, Maria C.
Abstract : Gastric cancer remains a significant worldwide health concern. While surgery is required for cure, all but the earliest of cancers will require multimodality therapy. Chemotherapy and chemoradiation in the neoadjuvant and adjuvant settings have shown to improve overall survival, but the sequencing of treatment is controversial. As healthcare expenses surge, it is increasingly important to impart value to these treatments. This review will look at the intersection of effective treatment and costs for gastric cancer. J. Surg. Oncol. 2016;114:296–303 . © 2016 Wiley Periodicals, Inc.